2009
DOI: 10.1093/aje/kwn390
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Psychosocial Hazards and the Association of Cumulative Lead Dose With Cognitive Function in Older Adults

Abstract: Before the 1970s, today's older Americans were exposed to high levels of lead in the environment. The authors previously reported that lifetime cumulative lead dose was associated with lower cognitive test performance in older adults. Experiments suggest that environmental stress may intensify the detrimental influence of lead. No large, population-based studies of this question have been done. The authors evaluated whether cross-sectional associations of tibia lead with cognitive function were modified by nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 54 publications
5
47
0
Order By: Relevance
“…This scale is well established; it has been described and used in previous literature to represent neighborhood-level exposures to psychosocial hazards in this same study population, and has been shown to have both main effects with health outcomes and exhibit effect modification of other exposures in their relation with health outcomes in prior analyses. 50,64 …”
Section: Strengthsmentioning
confidence: 99%
“…This scale is well established; it has been described and used in previous literature to represent neighborhood-level exposures to psychosocial hazards in this same study population, and has been shown to have both main effects with health outcomes and exhibit effect modification of other exposures in their relation with health outcomes in prior analyses. 50,64 …”
Section: Strengthsmentioning
confidence: 99%
“…Shaw and McKay (1969), Burgess (1925), Suttles (1968), and others developed theory and methods to characterize neighborhood context and construct neighborhood boundaries. Contemporary elaborations to these foundational theories have led to a resurgence in research that examines the links between neighborhood and educational attainment, criminal activity, risky behavior, and, our focus here, health (DeLuca & Dayton, 2009;Glass et al, 2009;Maimon & Browning, 2010;Moore, Roux, Nettleton, Jacobs, & Franco, 2009;Votruba & Kling, 2009). Attribution for growing interest in this area often rests on methodological advancements, such as hierarchical linear modeling (HLM) or geographic information systems (GIS), which allow for a more advanced treatment of multiple levels of infl uence and exacting depictions of physical space (Raudenbush & Bryk, 2002).…”
Section: Theory Of Neighborhood Contextmentioning
confidence: 99%
“…Yet, there is little empirical research examining neighborhood social stressors as a vulnerability factor in the relationship between environmental hazards and cognitive function. One prior study found that living in stressful neighborhoods amplified the adverse influence of environmental lead exposure on cognitive function (Glass et al, 2009). To our knowledge, however, no study to date has examined whether the relationship between air pollution and cognitive function is stronger among those living in more stressful neighborhoods.…”
Section: Introductionmentioning
confidence: 99%